Perubahan Sifat Delik dalam Pasal 2 dan Pasal 3 Undang-Undang Tindak Pidana Korupsi Pasca Putusan Mahkamah Konstitusi Nomor 25/PUU-XIV/2016 - Safrizal, Riyan Auliyanda; Fahmi Makraja; Ikhsan Fajri; Belia Pratiwi Rosadi (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This study discusses the shift in the meaning of delinquency in Articles 2 and 3 of the Corruption Crime Law (Corruption Law) which has an impact on law enforcement for corrupt perpetrators. In practice, the element of state losses must be clearly proven so that the perpetrator can be held criminally responsible. However, there is a phenomenon of corrupt perpetrators who return state losses to obscure the elements of loss as stipulated in Article 2 of the Corruption Law, so that they have the potential to escape criminal snare. This research uses a qualitative method with a descriptive analysis approach, through literature studies and studies of the Constitutional Court Decision Number 25/PUU-XIV/2016. The results of the study show that the basis of the applicants’ application in the decision is divided into four aspects, namely the authority of the Constitutional Court, the legal standing of the applicant, the object of the application, and the reason for the application. The Constitutional Court judge in the decision considered three main aspects, namely the authority of the Constitutional Court, the legal standing of the applicant, and the subject matter of the application. The judge’s legal considerations emphasized that the phrase "may" in Article 2 paragraph (1) and Article 3 of the Corruption Law caused legal uncertainty, so that the nature of the offense in the two articles changed to a formal offense. This has an impact on uncertain and fair legal protection for applicants and has serious implications for law enforcement of corruption crimes in Indonesia.